Strategi Guru Meningkatkan Literasi Penulisan Artikel Ilmiah Siswa Kelas XI MA Unggulan K.H. Abd. Wahab Hasbulloh Tambakberas Jombang - Izzatul Amaliyah; Waslah Waslah; Saihul Atho Alaul Huda (ANWARUL, 2026)
The low level of student literacy remains an important issue in education, particularly in developing the ability to write scientific papers, which requires interest, academic skills, and support from the learning environment. This study aims to analyze teachers’ strategies for improving literacy in scientific article writing among grade XI students at Madrasah Aliyah Unggulan K.H. Abd. Wahab Hasbulloh Bahrul Ulum Tambakberas Jombang. This study used a qualitative approach with a case study design. The research subjects included scientific article supervising teachers and grade XI students. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The results showed that teachers’ strategies for improving literacy in scientific article writing were implemented through the introduction of the form and structure of scientific articles, scientific article writing training, independent learning, and guidance in accessing and utilizing scientific articles as references. The supporting factors for these strategies included madrasah support in the form of internet access, a madrasah journal, and digital devices, intensive guidance from teachers, and students’ internal factors. Meanwhile, the inhibiting factors included limited research time, students’ perception that writing scientific articles is a difficult task, and limited device access among some students. The strategies implemented by teachers had an impact on improving students’ literacy and understanding, their ability to utilize technology, and their participation in scientific competitions organized by the government. The conclusion of this study confirms that improving students’ literacy in scientific article writing is influenced by effective collaboration among the madrasah, teachers, and students. The implications of this study indicate the importance of integrating digital literacy and intensive guidance into the madrasah curriculum to strengthen students’ academic readiness in the digital era.